Sibling Rivalry in Educational Attainment: The German Case - Ira N. Gang; Thomas Bauer (Rutgers University, Department of Economics, 2000)
Recent studies exploring sibling rivalry in the allocation of household resources in the U.S. produce conflicting results. We contribute to this discussion by addressing the role of sibling rivalry in educational attainment in Germany. Using the German Socioeconomic Panel (GSOEP) we are able to distinguish how the effects of sibling rivalry vary by cultural affiliation, i.e., among families of West German, East German and foreign origin. We also point out and correct for a reference group problem in earlier papers analyzing sibling rivalry.
Keywords: J24; 330; education; ethnicity; gender; human capital formation; sex composition